The Effects of Relationship Marketing and Strategic Innovation on Long-Term Competitive Advantage in Changing Market Conditions - Ahmed Sameer. N. Al-Thabit (Research Parks Publishers, 2026)
In today’s volatile business environments, marked by fast technological change, customer preferences that keep shifting, and global disruptions, firms have to develop sustainable competitive advantages over time. This conceptual paper looks at how relationship marketing (RM) and strategic innovation work together to shape long-term competitive advantage (CA). Based on the Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT), RM helps firms build relational resources and nurture repeat trust, basically customer loyalty. Strategic innovation in turn supports adaptation, and also enables differentiation, so the firm can keep moving forward even when the market behaves oddly. When these two efforts are combined, they can strengthen resilience and drive better performance in dynamic markets. The paper then proposes a general framework and discusses what it means for both theory and day to day practice.